Towards an in vitro assay : biomarker validation for facial eczema tolerance in sheep : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science [MSc] in Animal Science at Massey University, Manawatū, New Zealand - Bramley, Claudia May (Massey University, 2024)
Introduction: Facial eczema (FE) is a photosensitisation disease of grazing ruminant livestock caused by the ingestion of the fungal metabolite sporidesmin which is found in the spores of the fungus Pseudopithomyces chartarum. It is of huge concern to the sheep industry as it effects animal production and welfare. Several strategies to mitigate the effects of FE have been explored, however, breeding for increased tolerance has been recognised as the most effective management strategy. The current practice to test for FE tolerance is to dose rams with a controlled amount of sporidesmin and then observe the effects 21 days later which, from animal welfare and farming perspectives is unsustainable long-term and therefore an alternative test is needed. Recent advances have encouraged the development of an in vitro assay based on easily accessibly samples from individual animals which will remove the risks associated with animal welfare and accelerate FE tolerance in flocks. Aim: The hypothesis for this project was that the differential expression and prognostic values of the nine biomarkers identified during earlier work can be reproduced in a different set of sheep. Materials and methods: Peripheral blood mononuclear cells (PBMCs) were prepared from whole blood samples collected from sheep (n=290) on 13 farms enrolled in the Ramguardᵀᴹ programme, and an in vitro sporidesmin toxicity assay was performed. Total RNA was extracted from the PBMC pellets, subsequent to sporidesmin toxicity assay, using either the Qiagen Kit method or the Zymo Kit method. NanoString analysis of nine genes of interest and three reference genes was performed on 100 RNA samples and statistical analysis was carried out on each target gene between the FE tolerant and susceptible groups. The study animals were categorised into susceptible and tolerant groups based on the change in Gamma-Glutamyl Transferase levels (ΔGGT), before (day 0) and 21 (day 21) days subsequent to in vivo sporidesmin dosing. Results: The change in GGT levels (ΔGGT) was found to be 916.90 ± 489.30 IU/L for susceptible animals and 8.57 ± 9.80 IU/L for tolerant animals. Variability in GGT levels in animals between farms revealed different proportions of tolerant and susceptible rams across farms. There was no difference in RNA yield according to FE status (susceptible or tolerant), however there were differences in RNA yield and ΔGGT between the 13 farms. Of the nine biomarkers1 examined in this study, only four (ACP7, CCL27, LOC106990188 and TXN2) were significantly different between the susceptible and tolerant groups (p<0.05). Sensitivity and specificity were calculated for each of the four biomarkers individually and it was found that CCL27 had high specificity (0.80) and low sensitivity (0.34) while both TXN2 and LOC106990188 had high sensitivity (0.80) and low specificity (0.41). The four biomarkers were also combined in an attempt to improve individual prognostic values, and it was found that ACP7 combined with CCL27 resulted in a sensitivity of 0.37 and a specificity of 0.73. ACP7xCCL27 has a sensitivity of 0.31 and specificity of 0.75. Both ACP7+LOC106990188 and ACP7-TXN2 combinations have a sensitivity of 0.80 however, ACP7+LOC106990188 has a specificity of 0.46 while ACP7-TXN2 has a specificity of 0.23. Conclusion: Of the nine biomarkers investigated, the four markers (ACP7, CCL27, LOC106990188 and TXN2) were differentially expressed between the susceptible and tolerant groups, thereby indicating their potential to be used in a prognostic test for FE tolerance in sheep.
Keywords: 300304 Animal protection (incl. pests and pathogens); 300908 Veterinary mycology